2009
DOI: 10.1128/jb.01700-08
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid Capture by the Bacillus thuringiensis Conjugative Plasmid pXO16

Abstract: Conjugation, mobilization, and retromobilization are three related mechanisms of horizontal gene transfer in bacteria. They have been extensively studied in gram-negative species, where retromobilization, the capture of DNA from a recipient by a donor cell, was shown to result from two successive steps: the transfer of the conjugative plasmid from the donor to the recipient followed by the retrotransfer of the mobilizable plasmid to the donor. This successive model was established for gram-negative bacteria bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 40 publications
(49 reference statements)
0
29
0
Order By: Relevance
“…Beside its own transfer, the conjugative system of pXO16 is also able to mobilize and retro-mobilize many plasmids, including those lacking mob and oriT regions Timmery et al, 2009). The retro-mobilization mechanism follows a "successive" model, meaning that pXO16 has to transfer itself first into a recipient cell before it can "retro-mobilize" a plasmid from this recipient to the donor bacteria (Timmery et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Beside its own transfer, the conjugative system of pXO16 is also able to mobilize and retro-mobilize many plasmids, including those lacking mob and oriT regions Timmery et al, 2009). The retro-mobilization mechanism follows a "successive" model, meaning that pXO16 has to transfer itself first into a recipient cell before it can "retro-mobilize" a plasmid from this recipient to the donor bacteria (Timmery et al, 2009).…”
mentioning
confidence: 99%
“…The retro-mobilization mechanism follows a "successive" model, meaning that pXO16 has to transfer itself first into a recipient cell before it can "retro-mobilize" a plasmid from this recipient to the donor bacteria (Timmery et al, 2009).…”
mentioning
confidence: 99%
“…However, Timmery et al (2009) also demonstrated the retromobilization abilities of the conjugative plasmid pXO16 of B. thuringiensis subsp. israelensis, which were compared with the conjugation and mobilization abilities of this plasmid using mobilizable plasmids and a nonmobilizable element lacking the mob gene and oriT site.…”
Section: The Conjugation Process In B Thuringiensismentioning
confidence: 98%
“…Two different systems were described: the classical triparental matings are made using a donor, a recipient and a helper strain, which can transfer a mobilizable plasmid or a nonmobilizable plasmid, as detected by Timmery et al (2009). In this system transfer of a conjugative plasmid from the donor to the recipient and to the helper strain may occur as well as, mobilization of the plasmid from the helper strain to the recipient, transfer of both plasmids to the recipient, and retromobilization of the plasmid from the helper strain to the donor.…”
mentioning
confidence: 99%
“…Selective pressure and HGT, combined with recombination and shuffling between toxin genes (resulting in domain swapping) and sequence divergence, has yielded a wide range of host specificities for these insecticidal toxins [235,[285][286][287]. The genes encoding the crystal protein toxins, for example, are frequently clustered on different transmissible plasmids or transposable elements [235,[285][286][287][288], and conjugation between different strains has been observed in the soil environment and within insect guts [289][290][291][292]. Individual toxins have insecticidal activity only against a limited range of insect species (i.e., usually only within certain insect orders).…”
Section: Toxin Evolution In the Guts Of Insects And Other Vectorsmentioning
confidence: 99%